Front Cover: Theoretical and experimental analysis of negative dielectrophoresis‐induced particle trajectories. Issue 12 (14th June 2022) - Luna, Ramona; Heineck, Daniel P.; Bucher, Elmar; Heiser, Laura; Ibsen, Stuart D.
Abstract : DOI: 10.1002/elps.202100372 The front cover picture shows spherical particles acting under the influence of dielectrophoretic forces generated by a microelectrode array. These dielectrophoresis‐based forces were observed to be the main contributors to particle motion under high conductance media conditions resulting in the particles taking reproducible trajectories following the gradient of the nonuniform electric field. Here, negative dielectrophoresis is pushing these particles to the global minima region of the electric field located between the two electrodes. The symmetry of the electrode array causes particles to take paths with similar symmetrical shapes depending on their starting location. Knowing what forces influence the path that particles will take can help spatially direct them within the microfluidic chip device for detection and recovery applications.